STRENGTHENING ISLAMIC BOARDING SCHOOLS THROUGH DIVERSIFICATION OF NETWORK ORGANIZATIONS - Azizah, Nur; Yuliastuti, Emilda; Faradesi, Nazil (FORPIM PTKIS ZONA TAPAL KUDA, 2025)
This study aims to examine how the diversification of the organization of the pesantrennetwork can be an indicator so that the pesantren can operate effectively, encouragegrowth and be committed to participating in advancing the pesantren. This researchuses a qualitative approach with the type of Field Research, and the data collectionuses observation, interviews and documentation. The data obtained is then checked forvalidity through Credibility with triangulation techniques of sources and methods,transferability (transferability test), dependability (dependability test), andconfirmability (confirmability test). From the data collected, it was analyzed usinginteractive analysis from Miles and Huberman through several stages, namely: 1) DataCollection, 2) Data Condensation 3) Data Display 4) Drawing conclusions. The resultsof the study show that the existence of an Islamic boarding school networkorganization can be an indicator of strengthening Islamic boarding schools. Theexistence of the organization under the auspices of the Islamic boarding school hasimplications for the development of the pesantren in achieving a greater vision andmission so that the pesantren as an Islamic educational institution becomes anadaptive Islamic educational institution, namely able to face all the challenges of thetimes and can adapt to the changing times.